Ambivalent desires : representations of modernity and private life in Colombia (1890s-1950s) - Andrade, María Mercedes, 1971- (Bucknell University Press ; Rowman & Littlefield, 2011)
Ambivalent Desires is a literary and cultural study of the reception of modernity in Colombia. Unlike previous studies of Latin American modernization, which have usually focused on the public aspect of the process, this book discusses the intersection between modernity and the private sphere.